Preliminary efficacy and mediators of interpersonal psychotherapy for reducing posttraumatic stress symptoms in an incarcerated population. (17th February 2020) - Felton, Julia W.; Hailemariam, Maji; Richie, Fallon; Reddy, Madhavi K.; Edukere, Sophia; Zlotnick, Caron; Johnson, Jennifer E.
Abstract : Objective: Incarcerated individuals have high rates of trauma exposure. IPT reduces posttraumatic stress disorder (PTSD) symptoms in non-incarcerated adults, but has not been examined in prison populations. Moreover, little is known about the mechanisms through which IPT reduces PTSD symptoms. The current study investigated the direct and indirect effects of IPT on PTSD symptoms. We hypothesized that IPT would decrease PTSD symptoms by enhancing social support and decreasing loneliness (theorized IPT mechanisms). Method: A sub-sample of trauma-exposed participants ( n  = 168) were drawn from a larger randomized trial ( n  = 181) of IPT for major depressive disorder among prisoners. We examined a series of mediation models using non-parametric bootstrapping procedures to evaluate the indirect effect of IPT on PTSD symptoms. Results: Contrary to hypotheses, the relation between IPT and PTSD symptoms was significantly mediated through improvements in hopelessness and depressive symptoms (mechanisms of cognitive behavioral interventions), rather than through social support and loneliness. Increased social support and decreased loneliness were associated with decreased PTSD symptoms, but IPT did not predict changes in social support or loneliness. Conclusions: IPT may reduce PTSD symptoms in depressed prisoners by reducing hopelessness and depression. (ClinicalTrials.gov number NCT01685294)